ANALYSIS TYPES OF CODE-MIXING IN AZKA & DEDDY CORBUZIER UTTERANCES IN “DEDDY CORBUZIER” PODCAST: SOCIOLINGUISTIC APPROACH - Natalia Krisna; Juni Arta Sagala; Nurma Dhona Handayani (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2022)
This study applied a sociolinguistic study to obtain the types of Code mixing in the Podcast "Deddy Corbuzier". The purpose of this study was to analyse the types of code mixing contained in the podcast. Then, the speech was analyzed and categorised using the Musyken (2000) theory to the data source. The data source for this research was the code mixing uttered by Azka as guest star and Deddy Corbuzier. To get the desired research results, the research method used was descriptive qualitative method. Data collection technique was using observation technique and non-participation technique. Furthermore, because there was a vast volume of comparable data, the researchers applied the data reduction method. The data from this study was analysed using sociolinguistic approach. The researchers found utterances of code mixing in the speech of the guest star. As the result of the research, the researchers found 3 types of code mixing, including (9) Insertion, (4) Alternation, (2) Congruent Lexicalization. Insertion is the most common kind found in the data source, followed by Alternation and Congruent Lexicalization